Microcomputed tomography (micro-CT) analysis of apical mandibular premolar in relation to clinical sign presentation: An in vitro study - Samsudin Nurulaqmar Iwani; Marlena Kamaruzaman; Afiq Azizi Jawami (Saudi Dental Journal)
Introduction: Variations in anatomic apex and apical foramina of root canals are common in different teeth types. The sophisticated 3D micro-CT aids researchers in investigating the apical morphology, such as the apical foramen (AF) and constriction (AC). Objectives: To measure the length between the foramen and the apex and the physiological length to the apex, in lower premolar teeth. Furthermore, a measurement was conducted on the average length from the foramen to the apex of the lower premolar teeth with respect to the presence of clinical and non-clinical signs. Methods: A total of 80 lower premolar teeth were selected based on the inclusion criteria. All samples were scanned using micro-CT ZEISS X-Radia (17 µm), and the datasets were analysed. The root canal AF and AC were reconstructed using Drishti software (V3.0) by utilising a 4-digit system code in millimetres (mm). Results: More than half of the lower premolars (n = 47, 58.8 %) demonstrated a clinical signs presentation, while the rest had a non-clinical sign (n = 33, 41.3 %). There was a significant difference (p = 0.013) between the non-clinical and clinical groups in the mean length from the apical foramen to the apex (AFA) at 0.59 mm and 0.47 mm, respectively. Meanwhile, the non-clinical and clinical mean length from apical constriction to apex (ACA) were 0.75 mm and 0.73 mm, and the mean length from AF to AC (AFC) was 0.48 mm and 0.53 mm, respectively. Nonetheless, no significant differences were detected between the ACA and AFC of non-clinical and clinical groups. Conclusion: The clinical signs presentation observed in lower premolars mainly affected the apical morphology, particularly the position and length of the root AF, and less so the AC position and length. Therefore, the information is useful for clinical purposes.